Histochemical Studies on the Peyeras patches of Sheep (Ovis aries) (Global Journal of Medical Research, 2012)
Tissue pieces of jejunum and ileum from different prenatal and postnatal age groups of sheep were collected from Corporation slaughter house, Perambur, Chennai. The goblet cells in the villous epithelium were positive for Periodic acid Schiff (PAS) but the negative reaction was observed in the follicle-associated epithelium as the goblet cells were absent. The follicleassociated epithelium showed positive activity for the alkaline phosphatase. The activity was more intense over the follicle domes in all the prenatal and postnatal age groups. An intense acid phosphatase activity was observed in the follicle-associated epithelium and dome areas of Peyer#x2019;s patches. A linear activity of the adenosine triphosphatase was observed in the capsule of the ileal follicles and a mild enzyme activity was noticed in the interfollicular region. A reticular pattern of 5#x2019;nucleotidase enzyme activity was observed in the follicles of ileal Peyer#x2019;s patch.
Keywords: Sheep; Peyer#x2019; s patches; Histochemistry